SURVEY OF TOURISTS' SATISFACTION LEVEL WITH POST COVID 19 TAMANI FAITH TOURISM OBJECTS YEAR 2023 - Manurung, Jenny S; ibrahim, ibrahim (Journal of Physical Education, Health and Sports Recreation, 2023)
This research aims to obtain empirical facts about a survey of tourist satisfaction levels with the Taman Iman tourist attraction after Covid 19 in 2023. This type of research is descriptive research, namely research conducted on independent variables without making comparisons or connecting them with other variables. Descriptive research is not intended to test a particular hypothesis, but only describes "what is" about a variable, symptom or situation. The research location or place where the research was carried out was in Dairi Regency. The research was carried out in April 2023 and was carried out for 2 weeks. In this research, the sample that will be taken is 100 respondents. Data collection in this research was through questionnaires. A questionnaire is a data collection technique that is carried out by giving a set of questions or written questions to respondents to answer. The scale used is a Likert scale. The data analysis technique used is the percentage formula. The results of the research can be concluded that out of the 100 respondents, they had a very good level of satisfaction with the Taman Iman tourist and recreational objects. The questionnaire score obtained was 20736 and obtained a percentage of 86.4 in the very good category after Covid 19. Based on the data obtained, on average each item obtained a percentage above 80%, meaning that all items were in the very good category after Covid 19. And tourist satisfaction with tourist attractions Taman Iman is very good after Covid 19.